2021
DOI: 10.1007/s00068-021-01797-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hip fracture care in Europe: a systematic review of recent annual reports of hip fracture registries

Abstract: Purpose Hip fractures are of growing interest due to their increasing number, subsequent functional decline and high institutionalization rate of patients, mortality, and costs. Several process measurements are essential for hip fracture care. To compare and improve these, hip fracture registries in Europe became popular. This systematic review aims to describe the differences between hip fracture registries in Europe as well as the differences in hip fracture treatment between countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 55 publications
2
24
0
1
Order By: Relevance
“…The pooled estimate for one-year mortality (24.2%) was similar to rates estimated by a recent international systematic review [2] and those reported by the Danish national audit, which has the benefit of unambiguous registry linkage [24]. The pooled estimate for 30-day mortality (4.7%) was however low in comparison to robust sources in other similar European countries, which range from 5.5 to 9.5% [24]. It is unclear whether this represents a true difference or if it is an indication of under-estimation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The pooled estimate for one-year mortality (24.2%) was similar to rates estimated by a recent international systematic review [2] and those reported by the Danish national audit, which has the benefit of unambiguous registry linkage [24]. The pooled estimate for 30-day mortality (4.7%) was however low in comparison to robust sources in other similar European countries, which range from 5.5 to 9.5% [24]. It is unclear whether this represents a true difference or if it is an indication of under-estimation.…”
Section: Discussionsupporting
confidence: 83%
“…All-cause hospital re-admission may be easier to capture and for patients to self-report. It has been included in a core outcome set for orthogeriatric management of hip fractures and is collected as an outcome in several European hip fracture audits [11,24]. A small minority of Irish studies collected quality of life, and none used the EQ-5D measure that is recommended by the hip fracture core outcome set and integrated into several hip fracture audits internationally [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only 75% of Irish hip fracture patients are operated on within 48 h of admission [ 2 ]. This is in contrast to countries such as Germany and Sweden where 72% and 66% of patients respectively are operated on within 24 h of admission [ 18 ]. An Orthogeriatric model of care has also been shown to reduce time to surgery, improve the overall quality of care and enhance patient outcomes [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…A recent review of European national hip fracture audits concluded that hip fracture registries were a good tool with which to compare hospitals within one country, 22 but that they need to make the data they collect and present more uniform if international comparisons are to become feasible.…”
Section: Introductionmentioning
confidence: 99%